Smallholder farmers expand production area of the perennial crop enset as a climate coping strategy in a drought-prone indigenous agrisystem - Chase, Rachel; Roux, Nicolas; Borrell, James; Buchi, Lucie; Rodenburg, Jonne; Wendawek, Abebe M. (Wiley, 2023)
Climate resilient crops will become increasingly important, especially in regions where smallholder farmers are vulnerable to climate extremes. Enset, a multipurpose perennial staple crop consumed by over 20 million people in Ethiopia, purportedly provides food security during periods of drought. Here, we find evidence that fre-quent severe drought events led to an increase in enset production area. This is con-sistent with a broader pattern whereby farmers preferentially cultivate perennial and storable crops after long-term drought events, providing an example of adaptation to fluctuations in climate through crop choice in indigenous agrisystems.